The Effect of Social Media Personal Branding and Digital Literacy on The Employability of Management Students at Palangka Raya University in The Gig Economy Era - Kurnia Sukmaputra, Roni; Oktavia, Indah Nur; Muliyani, Agustina (Journal Research of Social Science, Economics, and Management, 2026)
The dynamics of the global labour market, which are shifting towards the gig economy era, require university graduates to possess the ability to adapt to technology and to market themselves effectively. This research is motivated by concern over the low job readiness among students, which is attributed to the tendency to use social media solely as a means of entertainment and to a lack of understanding of digital literacy. Departing from this phenomenon, this study was conducted to examine the extent to which personal branding on social media and digital literacy contribute to the job readiness of Management students at the University of Palangka Raya. This study employs a quantitative approach with a causal-associative design. Data were obtained through a questionnaire survey administered to active students who had completed at least four semesters, determined using the purposive sampling method, and were subsequently processed using multiple linear regression analysis. The findings of the study show that personal branding on social media and digital literacy each have a positive and significant impact on job readiness. When considered simultaneously, these two variables exerted a significant positive influence, with a combined contribution of 69.3%. The conclusions of this study emphasise that the combination of technical mastery through digital literacy and the ability to communicate one’s competencies through personal branding creates a synergy that is instrumental in shaping the profile of graduates who are ready to compete in the modern labour market.